Truth and honesty in Albert Camus's absurd hero, Meursault - Shobeiri, Ashkan; Wan Yahya, Wan Roselezam (EduSoft Publishing, 2011)
Many writers had already elaborated upon matters of truth and honesty, when Albert Camus characterized Meursault, the protagonist of his best selling novel The Outsider, as an honest man who ‘refuses to lie...for the sake of truth’. At that time, Camus had an international fame in the world of literature, and he explained the novel and his absurd hero, Meursault, in a preface to an English language edition of L’Etranger. Yet, some commentators and critics found Camus’ s explanation strange and reacted against his commentaries. Chief among them is Conor Cruise O’Brien who believes that Meursault of the actual novel is not the same that Camus characterized in the explanation of the novel. O’Brien points out that Meursualt of the story lies, and he is indifferent to truth. This paper is a critical examination of O’Brien’s and other critics’ commentaries which stand for and against Camus’s own commentaries on his absurd character, Meursault, to lead us to the heart of the matter of Camus’s understanding of terms such as honesty and truth. In doing so, despite the fact that Camus is the creator of Meursault, his commentary on Meursault is analysed next to other critics’ commentaries, and not as a dominant one.